Accounting handbook 2013 - Shying, Mark.; Subramanian, Ram. (French's Forest, N.S.W. : Pearson Australia for CPA, 2013)
'The 2013 CPA Accounting Handbook provides students and educators with all the legally enforceable Australian Accounting Standards (aligned to IFRS), all with accompanying new technical editor notes. There have been important changes to the standards over the past twelve months which makes the 2013 Handbook with its Technical Editor Notes a'must-have' edition. The enhanced companion website for this title, www.pearson.com.au/highered/handbooks , will include the amending standards, and will be updated throughout 2013 with any further changes to the accounting standards, accompanied by technical editor notes. Students may also use the Student Self Test quizzes aligned to particular AASBs and with hints & references back to the Handbook as practice and preparation for exams.'--Publisher.
Conceptual framework -- Australian accounting standards -- Interpretations.
' Incorporating all the Australian Accounting Standards for financial reporting periods ending June 30 2013, as stated at 16 November 2012'--cover.
'CPA Australia'--cover.
Includes bibliographical references.
Keywords: Accounting -- Standards -- Australia; Accounting -- Australia